(untitled) (Indonesian Minority Justice Review, 2024)
This paper examines the role of legal mechanisms in resolving ethnic and religious tensions in Indonesia’s diverse society. Ethnic and religious conflicts remain significant challenges in Indonesia, with tensions often exacerbated by local politics, economic inequalities, and cultural differences. The study investigates the legal tools available for conflict resolution, such as the 1999 Law on Human Rights, the 2001 Law on Regional Autonomy, and the 2006 Law on Religious Harmony. Through legal analysis and interviews with conflict resolution experts, community leaders, and policymakers, the research assesses the effectiveness of these legal frameworks in mitigating inter-ethnic and inter-religious violence. The paper also explores alternative dispute resolution methods, such as community mediation and local peacebuilding initiatives. The findings indicate that while legal frameworks have contributed to managing some conflicts, they are often insufficient in addressing deeper structural issues, such as economic disparities and historical grievances. The paper concludes by recommending stronger enforcement of existing laws, the incorporation of traditional conflict resolution methods, and the promotion of inclusive governance to address the root causes of ethnic and religious tensions.